"Falasha" Religion: Ancient Judaism or Evolving Ethiopian Tradition? - Kaplan, Steven (The Jewish quarterly review, 1988)
This article considers recent research on the religion of the Beta Israel (Falasha), and in particular Kay Kaufman Shelemay's "Music, Ritual," and "Falasha History." Most scholars have, on the basis of an artificially static and ahistorical picture of the Beta Israel religion, depicted it as a form of ancient Judaism. In contrast, Shelemay contends that the Beta Israel's religious tradition developed around the fourteenth or fifteenth century and draws heavily on Christian Ethiopian sources. While generally favorable to her views, this article attempts to demonstrate that the development of Beta Israel religion was a more gradual process than she claims and continued into even later periods. Evidence to support this theory is drawn from oral traditions and Beta Israel literature.